Archetype Analysis Of The Main Characters In The Three Stooges - Syamsul Bahri; Raja Sungai Simbolon; Anastasya Dwika Simanjuntak; Steven Nikson Sitanggang (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This study delves into the portrayal of character archetypes in "The Three Stooges" through the lens of Jungian psychology, suggesting that by understanding these archetypes, individual can learn to choose and cultivate better personality traits, such as caring for friends, recognizing and managing one's ego, navigating the facade that social situations may necessitate, and addressing feelings of envy. The purpose of this study is to explore the portrayal of character archetypes in "The Three Stooges" through the lens of Jungian psychology, providing nuanced insights into the complexities of character portrayal in fiction. Employing a qualitative descriptive approach, through qualitative analysis and quantitative data, the study offers nuanced insights into character portrayal, enhancing comprehension of psychosocial dynamics in fiction. the research scrutinizes dialogues and scenes to unveil the embodiment of archetypal elements by Moe, Larry, and Curly. As findings the self archetype emerges as predominant having 50%, reflecting their journey towards personal growth and integration of conscious and unconscious elements, followed by the persona archetype with 37%, highlighting adaptation to social norms. Glimpses of the ego archetype having 7% reveal desires, self-perception, and social interactions, while moments depicting the shadow archetype having 7% unveil darker, repressed aspects, illuminating internal conflicts. This research underscores the enduring relevance of archetype theory in literary analysis. The study concludes that "The Three Stooges" predominantly exemplifies the self archetype, with Moe, Larry, and Curly's character portrayals reflecting significant personal growth and integration of conscious and unconscious elements, while also highlighting adaptation to social norms, desires, self-perception, social interactions, and internal conflicts.